2019
DOI: 10.3847/1538-4357/ab55dc
|View full text |Cite
|
Sign up to set email alerts
|

ALMA Observations of Atomic Carbon [C i] (3P1 → 3P0) and Low-J CO Lines in the Starburst Galaxy NGC 1808

Abstract: We present [C I] 3 P 1 → 3 P 0 , 12 CO, 13 CO, and C 18 O (J = 2 → 1) observations of the central region (radius 1 kpc) of the starburst galaxy NGC 1808 at 30-50 pc resolution conducted with Atacama Large Millimeter/submillimeter Array. Radiative transfer analysis of multiline data indicates warm (T k ∼ 40−80 K) and dense (n H2 ∼ 10 3−4 cm −3 ) molecular gas with high column density of atomic carbon (N CI ∼ 3 × 10 18 cm −2 ) in the circumnuclear disk (central 100 pc). The C I/H 2 abundance in the central 1 kpc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 89 publications
(149 reference statements)
2
21
0
Order By: Relevance
“…We smoothed our 350 GHz continuum map at the same resolution and the integrated flux in a 2 diameter region is 27.8 mJy. The continuum at 500 GHz observed with ALMA in Band 8 at 0.825 × 0.59 resolution is presented by Salak et al (2019). At the AGN position, the continuum peaks at 54 mJy and smoothing our 350 GHz continuum at the same resolution of the 500 GHz map, we derive a spectral index of α = 3.6.…”
Section: Continuum Emissionmentioning
confidence: 96%
See 1 more Smart Citation
“…We smoothed our 350 GHz continuum map at the same resolution and the integrated flux in a 2 diameter region is 27.8 mJy. The continuum at 500 GHz observed with ALMA in Band 8 at 0.825 × 0.59 resolution is presented by Salak et al (2019). At the AGN position, the continuum peaks at 54 mJy and smoothing our 350 GHz continuum at the same resolution of the 500 GHz map, we derive a spectral index of α = 3.6.…”
Section: Continuum Emissionmentioning
confidence: 96%
“…As shown in the previous section, with the CO(3−2) velocity field, we can see a tilt in the kinematic major axis towards the nucleus. ALMA observations of neutral atomic carbon, [CI], presented in Salak et al (2019) at a spatial resolution of 0.82 × 0.6 , show a remarkable resemblance to the CO(3−2) morphology and kinematics. They also reveal this tilted kinematics in the center.…”
Section: Kinematic Misalignment At the Center Of The Nuclear Spiralmentioning
confidence: 99%
“…Jiao et al (2019) found that the [C I] (1-0) luminosity correlates linearly with the CO (1-0) luminosity for the different types of galaxies (see also Jiao et al 2017). However, recent studies claim that caution is needed when the [C I] (1-0) line is used as a tracer of molecular gas mass in resolved galaxies because the physical conditions strongly affect the intensities (e.g., Salak et al 2019;Saito et al 2020;Miyamoto et al 2021). It is also predicted that the relative abundance of C I is enhanced in outflows and cosmic-ray (CR) dominated regions by destroying CO (Bialy & Sternberg 2015;Bisbas et al 2015;Papadopoulos et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Fine structure lines of atomic carbon, for example [C ], are an additional tracer to probe the cold molecular phase (e.g., Papadopoulos & Greve 2004;Valentino et al 2018). Observational studies in the local Universe have shown that CO and [C ] can coexist, suggesting that both transitions arise from the same regions (e.g., White et al 1994;Ikeda et al 2002;Israel & Baas 2002), though spatial variations could be present (e.g., Salak et al 2019). Analysis using simultaneously [C ] and multi-transition CO observations at high redshifts found agreement between the H 2 masses determined through the two different tracers (e.g., Weiß et al 2003;Alaghband-Zadeh et al 2013), corroborating the assumption that [C ] and CO usually coexist (Carilli & Walter 2013).…”
Section: Introductionmentioning
confidence: 99%